The SiPM-on-tile system of the CMS HGCAL - Laudrain Antoine (EPJ Web of Conferences)
For the CMS High-Granularity Calorimeter (HGCAL) for HL-LHC, scintillator tiles, readout with individual on-tile silicon photomultipliers (SiPMs), will be used where the radiation levels are expected to be less than 5 × 1013 neq/cm2. The scintillator tiles will be mounted on highly-integrated “tile-boards” (typical area 30 × 30 cm2) that host up to 108 tiles and their SiPMs, as well as front-end electronics, control and powering components. A dedicated LED system will be implemented to monitor stability e↵ects. We present recent developments for the HGCAL scintillator material and SiPMs, including quantification of the scintillator and SiPM radiation-damage impact, modelling of SiPM noise and its evolution with time, SiPM production testing and quality control plans, and tests of tile-boards in laboratories and beam tests.